MANAJEMEN PRODUKSI PENANGKAPAN IKAN NELAYAN DI KELURAHAN TONDONGGEU KECAMATAN NAMBO KOTA KENDARI PERSPEKTIF EKONOMI ISLAM - Ude, Siskana M (IAIN Kendari, 2023)
This research aims to analyze the management of fish production by fishermen in Tondonggeu Village, Nambo District, Kendari City, from the perspective of Islamic Economics. This qualitative study used methods such as observation, interviews, and documentation for data collection. Data analysis included data reduction, presentation, drawing conclusions, and validating the data through source, technical, and time triangulation. The findings indicate that production management in Tondonggeu Village involves functions like planning, organizing, directing, and controlling the production process. Furthermore, when viewed through an Islamic economic lens, production management aligns with principles such as using simple and eco-friendly fishing equipment and marketing catches without harmful chemicals.